Frequencies of A(TA)7TAA, G71R, and G493R mutations of the UGT1A1 gene in the Malaysian population - Yusoff, Surini; Van Rostenberghe, Hans; Yusoff, Narazah M; A.Talib, Norlelawati; Ramli, Noraida; Ismail, N Zainal A N; Ismail, W Pauzi W; Matsuo, Masafumi; Nishio, Hisahide (2006)
The A(TA)7TAA seems more common than the G71R and G493R mutations in the Malaysian population.